Economic reform policies: The Malaysian experience - Wan Abdullah, N.R. (2008)
The Malaysian economic policies are designed to increase growth, reduce poverty, and improve governance. Under the "New Economic Policy" (NEP) the objectives were to eradicate poverty and to redistribute wealth. The characteristics of the implementation processes of the NEP was that of government's intervention through direct involvement in the economic activities and commercial sector. Through the NEP years, the economic performance was among the best in the world. This paper describes the distinct features of the Malaysian economic policy and how they are moving forward. The analyses are based on various studies and are presented into two sti ges. First, the understanding of the key elements of the policies and the implementation processes, and second, on the effectiveness of policy.